The Effect of the PLEASE Strategy on Students’ Ability in Writing Descriptive Text at the Tenth Grade of SMA Negeri 5 Pematangsiantar - Sitinjak, Evi Roseria; Neni Purba, Christian; Lolo Siahaan, Bas (The Future of Education Journal, 2024)
This research aimed to find out the effect of Pick, List, Evaluate, Activate, Supply, End (PLEASE) teaching strategy to writing ability of tenth grade students of SMA Negeri 5 Pematangsiantar in writing descriptive text. This research was quantitative research. To get the answer for this research, the researcher used quasi-experimental design. This design involved two classes of the same level. The population of this research was tenth grade students of SMA Negeri 5 Pematangsiantar that tenth class. The sample of this research consisted of two classes, namely class X-6 using PLEASE teaching strategy as the experimental class and class X-2 use guided teaching strategy as the control class.To collect the data, the researcher used the test. The researcher used essay test as the instrument of the research.The result of the research showed that the effect of PLEASE teaching strategy was more significant than guided writing teaching strategy. It was proved by then t- test value (2,972)>t-table (1,995). It means that Ha was accepted and Ho was rejected.  The ability of students in writing a descriptive text in the experimental class was improved since they were taught by PLEASE teaching strategy. It can be conclude that Pick, List, Evaluate, Activate, Supply, End (PLEASE) teaching strategy has an effect to the writing ability of tenth grade students of SMA Negeri 5 Pematangsiantar in a descriptive text. It is recommended that the results of this research can used in order to develop the teaching strategy at school.